Pengaruh Model Quantum Learning Teradap Kemampuan Pemahaman Konseptual Matematis Siswa Mts - Juli Trisna Dewi; Ida Mawarda; Zainal Azis (Journal Mathematics Education Sigma [JMES], 2022)
Abstract. This study aims to determine: 1) The effect of the Quantum Learning model on the ability to understand mathematical concepts of students, 2) The difference in the ability to understand mathematical concepts between students who are taught by the Quantum Learning model and students who are taught by Direct Instructional. The population of this study is all students of class VIII The Even Semester of MTs Aisyiyah North Sumatra for the Academic Year 2019/2020, which consisted of 3 classes, while the sample in this study consisted of two classes selected using random sampling, so that all classes had the opportunity to be samples. The instrument used in this study consisted of 10 questions which were declared valid and reliable. The data in this study are quantitative data. The data analysis technique to test the hypothesis used in this study used SPSS with the use of paired difference test. The results showed that: 1) the Quantum Learning model had an influence on students' understanding of mathematical concepts by 33.9%, while the rest were other variables not examined in this study, 2) the results of understanding students' mathematical concepts by applying the quantum learning model obtained an average posttest score of 83 ,17 with the highest value of 100 and the lowest value of 65.00 and a standard deviation of 8.85, while using the direct instructional model the average posttest value was 71.50 with the highest value of 85.00 and the lowest value of 55.00 and a standard deviation of 7 ,67.Abstrak. Penelitian ini bertujuan untuk mengetahui: 1) Pengaruh model Quantum Learning terhadap kemampuan pemahaman konsep matematika siswa, 2) Perbedaan kemampuan pemahaman konsep matematis antara siswa yang diajarkan dengan model Quantum Learning dengan siswa yang diajarkan dengan Direct Instructional.Populasi penelitian ini adalah seluruh siswa kelas VIII Semester GenapMTs Aisyiyah Sumatera Utara Tahun Akademik 2019/2020 yang berjumlah 3 kelas, sedangkan sampel pada penelitian ini terdiri dari dua kelas yang dipilih menggunakan random sampling, sehingga semua kelas berpeluang menjadi sampel. Instrumen yang digunakan pada penelitian ini terdiri atas 10 pertanyaan yang dinyatakan valid dan reliabel. Data pada penelitian ini merupakan data kuantitatif. Teknik analisis data untuk menguji hipotesis yang digunakan pada penelitian ini menggunakan SPSS dengan penggunaan uji beda berpasangan. Hasil penelitian menunjukkan bahwa : 1) model Quantum Learningmemiliki pengaruhterhadap pemahaman konsep matematika siswasebesar 33,9%, sedangkan sisanya merupakan variabel lain yang tidak diteliti pada penelitian ini, 2) hasil pemahaman konsep matematis siswa dengan menerapkanmodel quantum learningdiperoleh nilai rata-rata postes sebesar 83,17 dengan nilai tertinggi 100 dan nilai terendah 65,00 serta simpangan baku 8,85, sedangkan menggunakan model direct instructional diperoleh nilai rata-rata postes sebesar 71,50 dengan nilai tertinggi 85,00 dan nilai terendah 55,00 serta simpangan baku 7,67.